A Truly S-shaped Slot-loaded Broadband Microstrip Antenna for 5G Communication - Goswami, S.; Mandal, S. K.; Banerjee, S. (Advanced electromagnetics, 2025)
In this paper, a compact, microstrip-fed, wideband patch antenna loaded with a novel truly S-Shaped slot structure is proposed for the 5G communication systems. Firstly, a basic rectangular patch antenna with modified ground plane is designed with resonating frequency 3.13 GHz and bandwidth of 830 MHz from 2.65 GHz to 3.5 GHz. Then, an S-shaped slot, resembling the actual shape of the alphabet ‘S’ is introduced at the middle of the patch to achieve wideband operation from 2.7 – 5.6 GHz covering a part of the sub-6 5G communication band. In order to compare the performance of the truly S-shaped slotted antenna with that of the conventional one, another antenna with the abrupt 900 bending S-shaped slot is also designed and the performances of both the antennas are illustrated. With introduction of the slot, the resultant antenna resonates at two resonating frequencies 3.21 GHz and 5.45 GHz, corresponding to the operating modes TM10 and TMd0 of the patch and the slot, respectively. The proposed antenna offers wide operating bandwidth of 2.9 GHz with overall gain of ~2 dBi at both the resonating frequencies. A fabricated antenna prototype is used to validate the antenna performance with the simulated results.